2020
DOI: 10.5194/gmd-2020-164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Whole Antarctic Ocean Model (WAOM v1.0): Development and Evaluation

Abstract: Abstract. The Regional Ocean Modeling System (ROMS), including an ice shelf component, has been applied on a circum-Antarctic domain to derive estimates of ice shelf basal melting. Significant improvements made compared to previous models of this scale are the inclusion of tides and a horizontal spatial resolution of 2 km, which is sufficient to resolve onshelf heat transport by bathymetric troughs and eddy scale circulation. We run the model with ocean-atmosphere-sea ice conditions from the year 2007, to repr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 74 publications
(136 reference statements)
0
17
0
Order By: Relevance
“…-3-non-peer reviewed preprint A cold bias under some of the warm water ice shelves has been previously reported (Richter et al, 2020). Affected ice shelves are, e.g.…”
Section: Model Descriptionmentioning
confidence: 83%
See 2 more Smart Citations
“…-3-non-peer reviewed preprint A cold bias under some of the warm water ice shelves has been previously reported (Richter et al, 2020). Affected ice shelves are, e.g.…”
Section: Model Descriptionmentioning
confidence: 83%
“…We analyse a prediction of Antarctic ice shelf melting during 2007 derived with the Whole Antarctic Ocean Model (WAOM v1.0). The simulation and its evaluation is described in detail elsewhere (Richter et al, 2020), here we outline only the technical details relevant for this study. Major improvements of WAOM compared to previous largescale models are the inclusion of tides and an eddy resolving resolution.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 60 larger regional to global scale the challenges lie more with sea ice production and water mass formation as coupled models seek to combine the ocean, atmosphere and ice structure (e.g. Roach et al, 2018;Richter et al, 2020;Moorman et al, 2020). Uniformly these studies identify the need for more observations both at the process, and monitoring, scales.…”
mentioning
confidence: 99%
“…Following this water north, a number of studies have concluded that the ice shelf water from the Ross/McMurdo system persists for a hundred or more km northward (Hughes et al, 2014;Robinson et al, 2014). Richter et al (2020) state that ice shelf-sea ice-ocean connections remain the major outstanding challenge in models operating at the continental and global scale. Injection of the range of processes 425 described here into modelling approaches that typically resolve scales around 2 km will be a challenge.…”
mentioning
confidence: 99%